Exploration of Ethical Dilemmas and Legal Challenges Confronting Nonprofit Organizations and Their Governance Structures - Sahu, Sneha (Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement; Vol 1 No 1 (2025): Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement, 2025)
Nonprofit organizations are integral to addressing societal challenges, but they often encounter ethical dilemmas and legal challenges that impact their governance structures. This article explores the ethical and legal challenges that nonprofits face, including conflicts of interest, resource allocation, fundraising practices, and compliance with tax and employment laws. It also examines the role of governance structures in addressing these challenges, highlighting key strategies such as conflict of interest policies, financial oversight, and risk management frameworks. Through case studies, such as those involving the American Red Cross and Oxfam, the article illustrates how nonprofits can mitigate risks and maintain public trust. Ultimately, effective governance, ethical decision-making, and legal compliance are critical to ensuring the long-term success and integrity of nonprofit organizations.